Comparative Performance of SARS-CoV-2 Detection Assays Using Seven Different Primer-Probe Sets and One Assay Kit - Nalla, Arun K. (J Clin Microbiol, 2020)
Nearly 400,000 people worldwide are known to have been infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) beginning in December 2019. The virus has now spread to over 168 countries including the United States, where the first cluster of cases was observed in the Seattle metropolitan area in Washington. Given the rapid increase in the number of cases in many localities, the availability of accurate, high-throughput SARS-CoV-2 testing is vital to efforts to manage the current public health crisis. In the course of optimizing SARS-CoV-2 testing performed by the University of Washington Clinical Virology Lab (UW Virology Lab), we evaluated assays using seven different primer-probe sets and one assay kit. We found that the most sensitive assays were those that used the E-gene primer-probe set described by Corman et al. (V. M. Corman, O. Landt, M. Kaiser, R. Molenkamp, et al., Euro Surveill 25:2000045, 2020, https://doi.org/10.2807/1560-7917.ES.2020.25.3.2000045) and the N2 set developed by the CDC (Division of Viral Diseases, Centers for Disease Control and Prevention, 2020, https://www.cdc.gov/coronavirus/2019-ncov/downloads/rt-pcr-panel-primer-probes.pdf). All assays tested were found to be highly specific for SARS-CoV-2, with no cross-reactivity with other respiratory viruses observed in our analyses regardless of the primer-probe set or kit used. These results will provide valuable information to other clinical laboratories who are actively developing SARS-CoV-2 testing protocols at a time when increased testing capacity is urgently needed worldwide.